TINJAUAN SISTEM UPAH BURUH TANI DI KECAMATAN PAMIJAHAN, KABUPATEN BOGOR DALAM PERSPEKTIF HUKUM ISLAM - Asep Fahru Ramadhan; Ermi Suryani; Mohamad Kharis Mubarok (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
Payment of wages to agricultural workers in Pamijahan District, Bogor Regency is highly dependent on an oral agreement between the wage earner and the wage earner. The payer in this case is the land owner or his representative. Recipients of wages in this case are agricultural laborers. This study aims to determine the system of implementing agricultural labor wages, as well as knowing the views of Islamic law on the payment of agricultural labor wages in Pamijahan District, Bogor Regency. This study uses a qualitative approach, with a qualitative descriptive research type. The data used in this study were obtained through observation at the research site, direct interviews with relevant sources in Pamijahan District, Bogor Regency, as well as literature studies or document studies. The results of this study indicate that the system of wages for farm workers during the rice harvest in 4 villages in Pamijahan District, Bogor Regency is that for each farm worker, 5 gedeng of grain are received, so 1 gedeng is given as a wage for farm laborers, 4 gedeng is given to the land owner. In addition, farm workers receive food, drink, coffee and cigarettes. The wage system implemented has fulfilled the requirements in Islamic law.